Comparisons of Some Selected Physiological and Physical Aspects of Snow Skaters and Rock Climbers of Jammu and Kashmir - Nazir Ahmad Dar; Showkat Ahmad Dar (JUARA : Jurnal Olahraga, 2021)
Researchers have shown their interest in taking up this issue to assess and compare several physical and physiological variables between snow skaters and rock climbers JAMMU and KASHMIR. The investigators limited their studies to physical and physiological variables: flexibility, BMI, tidal volume, and cardiovascular endurance. The study was conducted on 60 players, all subjects were from JAMMU and KASHMIR, and the sampling technique adopted for topic selection from both groups was carried out through the random sampling method. Data for comparing various physical and physiological variables is collected through standardized and scientifically approved testing devices. The standard deviation calculated from the snow-skaters' four variables and rock-climbing JAMMU and KASHMIR, namely the mean and standard deviation of the rock climber's tidal volume, is (455.74 ± 78.94), and the mean and standard deviation of the tidal volume of the snow rate. Skaters were (497.3 ± 82.07), with a mean difference of 42.56. The mean and standard deviation of rock climbers' BMI were (20.76 ± 1.04) and snowboarding (23.54 ± 1.89), respectively, with a mean difference of 2.77. The mean and standard deviation of rock climber flexibility is (24.65 ± 4.3) and snow skater sane is (21.74 ± 4.01) with a mean difference of 2.91, mean and standard deviation of vo2 Max snow skater is (58.24 ± 3.68) and the mean and standard deviation of vo2max calculated from the rock climber is (70.4 ± 4.03) with a mean difference of 11.8. Therefore rock climbers were excellent at all BMI, lung tidal volume, and endurance but lower in flexibility than snow skaters. The practical implications of this study show that rock climbing is better for overall health than snowboarding. Not much effort is required for snowboarding as it is necessary for rock climbing, which may cause better physical and physiological development of the rock climbing profile.